2013
DOI: 10.1016/j.devcel.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

CHD5 Is Required for Neurogenesis and Has a Dual Role in Facilitating Gene Expression and Polycomb Gene Repression

Abstract: The chromatin remodeler CHD5 is expressed in neural tissue and is frequently deleted in aggressive neuroblastoma. Very little is known about the function of CHD5 in the nervous system or its mechanism of action. Here we report that depletion of Chd5 in the developing neocortex blocks neuronal differentiation and leads to an accumulation of undifferentiated progenitors. CHD5 binds a large cohort of genes and is required for facilitating the activation of neuronal genes. It also binds a cohort of Polycomb target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
138
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(144 citation statements)
references
References 57 publications
(72 reference statements)
5
138
1
Order By: Relevance
“…Taken together, these findings indicate the involvement of PcG proteins in two hallmarks of NEPC: metastasis and drug resistance. PcG proteins are also known to regulate stem cell differentiation and neurogenesis [49,50]. Loss of EZH2 in neuronal progenitor cells led to reduced proliferation and survival [51].…”
mentioning
confidence: 99%
“…Taken together, these findings indicate the involvement of PcG proteins in two hallmarks of NEPC: metastasis and drug resistance. PcG proteins are also known to regulate stem cell differentiation and neurogenesis [49,50]. Loss of EZH2 in neuronal progenitor cells led to reduced proliferation and survival [51].…”
mentioning
confidence: 99%
“…While the minimal deleted region contains CHD8 and the adjacent SUPT16H locus, the importance of abrogated CHD8 function in the phenotype of these patients is underscored by the identification of disruptive CHD8 mutations in individuals with DD or ASD [31] and recapitulation of a subset of features of the human phenotype in the zebrafish model [32]. Although other CHD proteins have yet to be linked to human genetic disease, it has been demonstrated that CHD4 and CHD5 carry out important functions in neurogenesis [33,34]. Although beyond the scope of this communication, the contribution of CHD dysfunction in the etiology of cancer has been long recognized [35].…”
Section: Chd Family and Genetic Diseasementioning
confidence: 99%
“…CHD1 chromodomains (Fig. 1) interact with lysine 4 of methylated histone H3 (H3K4me), and CHD5 chromodomains bind to and maintain lysine 27 of trimethylated histone H3 (H3K27me3) [11,12]. Thus, specific CHD chromatin remodeling proteins exhibit unique functions and preferences for repressive or active histone marks, and the methyl-histone-binding chromodomains are essential for maintaining dynamic chromatin structures and proper gene expression.…”
Section: Structure and Function Of The Chd Superfamilymentioning
confidence: 99%
“…Similar to CHD4, CHD5 also interacts with the PRC2 and specifically associates with the repressive histone modification H3K27me3 in neural stem cells [12]. CHD5 is highly expressed in neural progenitor and neuroblast cells of the SVZ and subgranular zone (SGZ) of the hippocampus, which produces neurons that are important for learning and memory [12].…”
Section: Chd Proteins and Neural Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation